A new technology in production of aerospace components: Powder injection molding (PIM) - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2003)
In recently years, Powder Injection Molding (PIM) is one of the powder metallurgy processes, which is gradually developing. The complex shaped and too much of a performance material can be produced by PIM process. This new production technology has a lot of excellent alternative comparison with other production process for metal and/or ceramic materials production. The mixing of binding and metal and/or ceramic powders are shaped in injection molds then the binding are removed and finally green materials are sintered after that the material is ready service. With all the characteristics, PIM requires high technology and economic and feasible process. Producing items with powder injection molding are being complicated and having high performance so using it about aviation is being avoided. Aviation industries product some materials that including tungsten, heavy alloyed items, titanium alloyed items,. stainless steel items and thermal fragments with ceramic objects with this technology. Items that producing with this technology are using on electronic components. Powder injection molding facilitated this technology too. On this study, Powder Injection Molding with general core processes described and its application on aviation industry examined detailed. After this observation, technology of powder injection molding's position and future is converseted. © 2003 IEEE.